A mixed methods study of the teachers’ self-efficacy views and their ability to improve self-efficacy beliefs during teaching - Orakcı, Şenol; Yüreğilli Göksu, Derya; Karagöz, Savaş (Frontiers in Psychology, 2023)
The current study has the aim of investigating teachers’ views about their self-efficacy and how they improve their self-efficacy beliefs during teaching practice. The study was designed in a mixed methods research design. “Teacher’s Self-Efficacy Scale”, “Personal Information Form” and “Semi-structured Interview Form” were employed in the study. The quantitative data were collected from 379 teachers in public schools in the 2021-2022 academic year, whereas the qualitative data were obtained from the top ten participants with the highest level of self-efficacy. The study is of great importance since determining teachers’ opinions about their self-efficacy beliefs and how they improve their self-efficacy beliefs in the solution of the problems they encountered during teaching practice will not only raise awareness of the importance of self-efficacy in teaching profession, but will contribute to further research and qualified teacher training.